Karakteristik Breakdown Voltage Pada Dielektrik Minyak Mineral dan Minyak Ester Natural - Hanifiyah Darna Fidya Amaral; Sungkowo , Heri; Handani, Galuh Prawestri Citra; Hermawan, Ahmad; Hermawan, Satria Luthfi; Ramadhana , Herlambang Kresna Adi; Agustin, Nabilla Dinda Tri (Elposys: Jurnal Sistem Kelistrikan, 2024)
The increasing demand for electrical energy, driven by population growth and industrial development, necessitates efficient and sustainable power distribution systems. Transformers, essential components of these systems, typically use mineral oil for insulation and cooling, despite its environmental drawbacks, such as high carbon emissions and non-biodegradability. In response, natural ester oils have emerged as eco-friendly alternatives. This study aimed to compare the dielectric breakdown voltage characteristics of mineral oil (Diala B) and natural ester oil (FR3) in transformer applications. The testing followed the IEC 60156 standard, focusing on transformers operating at 20 kV, with a minimum breakdown voltage threshold of 30 kV/2.5mm. Both treated and untreated samples were examined.The results indicated that FR3 ester oil exhibited superior dielectric properties, including higher breakdown voltage, flashpoint, and firepoint, as well as lower carbon emissions compared to mineral oil. These findings suggest that natural ester oil has significant potential as a sustainable replacement for mineral oil, particularly in applications where environmental and safety concerns are prioritized.The study recommends further long-term testing under operational conditions to confirm the performance and stability of ester oil in real-world transformer applications. These findings contribute to the growing body of research supporting the transition to more environmentally friendly transformer insulation materials, which could have broad implications for the power industry’s sustainability efforts